2020
DOI: 10.1126/sciadv.aay7633
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to both high safety and high performance of lithium-ion batteries

Abstract: We present a novel concept to achieve high performance and high safety simultaneously by passivating a Li-ion cell and then self-heating before use. By adding a small amount of triallyl phosphate in conventional electrolytes, we show that resistances of the passivated cells can increase by ~5×, thereby ensuring high safety and thermal stability. High power before battery operation is delivered by self-heating to an elevated temperature such as 60°C within tens of seconds. The present approach of building a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 14 publications
(16 reference statements)
1
62
0
Order By: Relevance
“…It has been revealed that elevating the operating temperature can reduce the cooling need by an order of magnitude due to reduced heat generation rates and enlarged temperature differences between cells and ambient. 50,53 The elevated temperature also boosts battery power capability. Furthermore, by adding electrolyte additives such as triallyl phosphate to passivate cathode and anode materials, the batteries exhibited exceptional safety and life.…”
Section: Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that elevating the operating temperature can reduce the cooling need by an order of magnitude due to reduced heat generation rates and enlarged temperature differences between cells and ambient. 50,53 The elevated temperature also boosts battery power capability. Furthermore, by adding electrolyte additives such as triallyl phosphate to passivate cathode and anode materials, the batteries exhibited exceptional safety and life.…”
Section: Future Outlookmentioning
confidence: 99%
“…Furthermore, by adding electrolyte additives such as triallyl phosphate to passivate cathode and anode materials, the batteries exhibited exceptional safety and life. 53 Indeed, the thermal modulation structure enables outstanding battery performance at low ambient temperatures, while the use of stable materials renders high safety and durability at high temperatures. Such a synergistic combination has the potential to achieve high-performance, durable, and safe eVTOL operation in all climates.…”
Section: Future Outlookmentioning
confidence: 99%
“…This property is achieved using triallyl phosphate (TAP) molecules which polymerize at the SEI at room temperature. [102] This reduces problems such as cell aging and self-discharge, leading to improved battery state of health. The passivated cells are completely resistant to the causes of TR.…”
Section: Electrolyte Compositionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) are one of the great successes of electrochemical energy storage devices utilized in diverse applications such as portable electronics, hybrid automobiles and even large-scale electrical power storage systems [1][2][3][4]. Since the first market emergence of LIBs in the 1990s, the performance of LIBs has been remarkably improved to meet the increasing demand for new energy storage systems with high energy density, high power density, long cycle life and a wide range of operating temperatures [5,6]. Moreover, rechargeable batteries are rapidly expanding to drivetrains [7,8], as can be seen from the quadrupled global sales of plug-in light vehicles from 0.55 to 2.21 million cars annually from 2015 to 2019 [9].…”
Section: Introductionmentioning
confidence: 99%